2007
DOI: 10.1242/jcs.03448
|View full text |Cite
|
Sign up to set email alerts
|

Nogo enhances the adhesion of olfactory ensheathing cells and inhibits their migration

Abstract: The migration of olfactory ensheathing cells (OECs) is essential for pioneering the olfactory nerve pathway during development and for promoting axonal regeneration when implanted into the injured central nervous system (CNS). In the present study, recombinant Nogo-66 enhanced the adhesion of OECs and inhibited their migration. Using immunocytochemistry and western blot, we showed that the Nogo-66 receptor (NgR) was expressed on OECs. When NgR was released from the cell surface with phosphatidylinositol-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 84 publications
2
57
0
Order By: Relevance
“…Therefore, the ability of OECs to migrate in the CNS is thought to be crucial for neural regeneration and re-ensheathment after spinal cord injury. Further to this, studies have shown that several factors are involved in the regulation of OEC migration [33,39,49]. Transplanted OECs face a more complex environment during their migration, as they interact with a greater variety of cell types (such as reactive astrocytes) and with the many factors that are produced through injury.…”
Section: S C O E C S T O a S T Y P E 1 O E C S A S T Y P E 1 O E C S mentioning
confidence: 99%
“…Therefore, the ability of OECs to migrate in the CNS is thought to be crucial for neural regeneration and re-ensheathment after spinal cord injury. Further to this, studies have shown that several factors are involved in the regulation of OEC migration [33,39,49]. Transplanted OECs face a more complex environment during their migration, as they interact with a greater variety of cell types (such as reactive astrocytes) and with the many factors that are produced through injury.…”
Section: S C O E C S T O a S T Y P E 1 O E C S A S T Y P E 1 O E C S mentioning
confidence: 99%
“…In fact, these observations raised the notion that OECs respond to a wide range of molecules. Indeed, Nogo-A (a MAI) enhances the adhesion of OECs affecting their migration (Su et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…RhoA Activation Analysis-RhoA activity in cell lysates was analyzed using a Rho activation assay kit (Millipore) according to the instructions of the manufacturer and our previous report (21). Briefly, CGN cultures were stimulated by GST or GSTNogo-66 (100 nM) (2) for specified time periods before being lysed in 250 l of supplied lysis buffer containing mixture protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Cultured CGNs were treated with Nogo-66 (100 nM) for several specified time periods. Afterward, RhoA activity was detected using a GST-fused Rho-binding domain of Rhotekin that could precipitate GTP-bound active RhoA (21). As shown in Fig.…”
Section: Rhoa Is Activated By Nogo-66 Stimulation In Both Wild-type Amentioning
confidence: 99%